Antioxidant Impact on Specific Antiviral Activity of Human Recombinant Interferon α-2b with Respect to Herpes simplex in Cell Culture - A. N. Vasilyev (Антибиотики и Химиотерапия, 2020)
In vitro synergistic antiviral effect of interferon α-2b in combination with unithiol (an antioxidant) on diverse variants of Herpes simplex, including the clinical acyclovir-resistant isolates, was demonstrated. Unithiol showed immediate antiherpes activity in the cell culture. However, its activity was lower than that of ascorbic acid, another highly active antioxidant. It was also observed that the specific antiherpes activity of interferon α-2b in the presence of unithiol increased several times. The data could be useful in the clinical practice, since the drugs combinations or complex formulations provide higher efficacy of the herpetic infection therapy with the use of the same concentrations of the available agents.